Ag85b/ESAT6-CFP10 adjuvanted with aluminum/poly-IC effectively protects guinea pigs from latent mycobacterium tuberculosis infection. Issue 32 (26th July 2019) - Wang, Chunhua; Lu, Jinbiao; Du, Weixin; Wang, Guozhi; Li, Xuguang; Shen, Xiaobin; Su, Cheng; Yang, Lei; Chen, Baowen; Wang, Junzhi; Xu, Miao
Abstract: The high global burden of tuberculosis (TB) underscores the urgent need for an effective TB vaccine since the only licensed Bacillus Calmette-Guérin (BCG) vaccine is ineffective in preventing adult pulmonary TB and affords no protection against latent TB infection (LTBI). Herein we investigated the potential of Mycobacterium tuberculosis ( Mtb ) antigen proteins AEC comprised of Ag85b and ESAT6-CFP10 proteins in conjunction with aluminum (Al) and polyriboinosinic-polyribocytidylic acid (poly- IC) as a novel subunit vaccine against TB. The immunogenicity and protection induced by the adjuvanted vaccine were evaluated in two animal models. Mice vaccinated with AEC/Al/poly- IC exhibited significant antigen-specific humoral immune responses and cell-mediated immunity as determined by immunoassay and multicolor flow cytometric assay, and the protective effect of the vaccine was demonstrated in a guinea pig model of latent Mtb infection. Compared to the control group, the mean pathological scores and bacterial loads in lungs and spleens of AEC/Al/poly- IC-immunized guinea pigs were significantly reduced. These data indicate that the AEC/Al/poly-IC is highly immunogenic in mice and can effectively protect guinea pigs against latent Mtb infection; it may represent a promising candidate vaccine for the control of latent TB.